2006
DOI: 10.1021/es0523035
|View full text |Cite
|
Sign up to set email alerts
|

A Stochastic Regression Approach to Analyzing Thermodynamic Uncertainty in Chemical Speciation Modeling

Abstract: Chemical speciation modeling is a vital tool for assessing the bioavailability of inorganic species, yet significant uncertainties in thermodynamic parameters and model form limit its potential for decision-making. In this paper we present a novel method for the quantification of thermodynamic parameter uncertainty and ionic strength correction model uncertainty using Bayesian Markov Chain Monte Carlo (MCMC) estimation methods. These methods allow for the inclusion of correlation modeling, which has not been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The approach thereby overcomes some of the bias introduced by a single detection window approach (Gledhill and Buck, 2012;Pizeta et al, 2015). Our approach in this study was empirical, and further rigor could be achieved with a statistically sound optimization of the results, once basic parameters such as the number and acidity of marine DOM binding sites were known with greater certainty (e.g., Weber et al, 2006). We found that incorporation of an inert phase was required in order to calculate Fe(NN) 3 concentrations to within an order of magnitude of measured Fe(NN) 3 concentrations in samples with high dissolved iron (Figure 5).…”
Section: The Nica-donnan Approachmentioning
confidence: 99%
“…The approach thereby overcomes some of the bias introduced by a single detection window approach (Gledhill and Buck, 2012;Pizeta et al, 2015). Our approach in this study was empirical, and further rigor could be achieved with a statistically sound optimization of the results, once basic parameters such as the number and acidity of marine DOM binding sites were known with greater certainty (e.g., Weber et al, 2006). We found that incorporation of an inert phase was required in order to calculate Fe(NN) 3 concentrations to within an order of magnitude of measured Fe(NN) 3 concentrations in samples with high dissolved iron (Figure 5).…”
Section: The Nica-donnan Approachmentioning
confidence: 99%
“…The use of MCMC methods in numerical water quality modeling is still rather limited but is anticipated to increase due to the significant advantages of the method for certain applications (5,6,(24)(25)(26). The Metropolis-Hastings algorithm (23) and the adaptive version of it (26,27) which we use in the MCMC simulation, are based on "guided" random walk in the parameter space.…”
Section: Model Uncertainty Analysis and Calibration: Mcmc Methodmentioning
confidence: 99%
“…Stochastic approaches can be utilized for correction of stability constants when the chemical environment of a system substantially deviates from original laboratory conditions (e.g. Weber et al 2006).…”
Section: Modelling Uncertaintiesmentioning
confidence: 99%